PENGEMBANGAN RENCANA BISNIS WIRAUSAHA MAHASISWA MELALUI PELATIHAN PENYUSUNAN FEASIBILITY STUDY BISNIS - Julita, Julita; Nasrizal, Nasrizal; Abdurrahman, Rezi; Iznillah, Muhammad Luthfi (Jurnal Abdi Insani, 2025)
Universities play a strategic role in fostering entrepreneurship, including through training in the preparation of Feasibility Studies (FS) to support the development of student entrepreneurship. This training aims to enhance students' understanding and competence in preparing FS relevant to their businesses, to reduce risks, facilitate planning, and improve business management. The methodology involves situational analysis, training preparation, material delivery, FS preparation workshops, and evaluation and mentoring. The material covers the importance of FS, the FS preparation process, and workshops using an interactive discussion approach. Results showed a significant increase in participants' understanding of FS, with most participants expressing readiness to implement the FS outcomes in their businesses. A total of 58 students from the UNRI Entrepreneur Society (UNRIES) demonstrated high enthusiasm throughout the training, which indicates the success of the applied methodology. This activity helped students understand financial needs, potential risks, and risk mitigation strategies for their businesses. With systematic and targeted training, the entrepreneurial competencies of Universitas Riau students were successfully improved. This training was effective in preparing students to run businesses more strategically and systematically, thereby supporting sustainable entrepreneurship development.